PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Sari, Terigas; Sulistri, Emi; Anitra, Rien (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to determine whether there is an effect of the cooperative learning model of the Group Investigation type assisted by Canva on fifth-grade students’ learning outcomes in IPAS at SDN 29 Singkawang. The research used a quasi-experimental design, specifically a one-group pretest-posttest design. The population of this study consisted of fifth-grade students at SDN 29 Singkawang, with total sampling used as the sampling technique. The results showed that: (1) there is a significant effect of the Group Investigation cooperative learning model assisted by Canva on students' IPAS learning outcomes. This is evidenced by the Wilcoxon test result where the z_calculated value was 21.53, while the z_table value was 1.96, indicating that z_calculated ? z_table. The effect size test yielded a value of 1.28, which indicates a high effect of the Canva-assisted Group Investigation model on student learning outcomes; (2) there was an improvement in students’ learning outcomes after using the Canva-assisted Group Investigation model. This is supported by the N-Gain test result of 0.45, which falls into the medium category with a percentage gain of 45%. Based on these findings, the Canva-assisted Group Investigation learning model can be used as an alternative model and media for teaching.